A new Plotosaurini mosasaur skull from the upper Maastrichtian of Antarctica. Plotosaurini paleogeographic occurrences - González Ruiz, Pablo; Fernández, Marta Susana; Talevi, Marianella; Leardi, Juan Martín; Reguero, Marcelo Alfredo (Cretaceous Research)
During the Antarctic summer campaigns and as a result of paleontological fieldworks 2013–2015 several mosasaur remains have been collected from the upper Maastrichtian López de Bertodano Formation exposed at Marambio (=Seymour) Island, of the Antarctic Peninsula. One of these specimens preserves part of the skull and dentition, which represent one of the few known skulls from Antarctica. The new specimen (MLP 15-I-24-41) is similar to member of the mosasaur tribe Plotosaurini, sharing the same fronto-parietal suture pattern, and a similar dental morphology as some of the species assigned to the genus. As the specimen is not complete enough to propose a new name it is referred to Mosasaurus sp. The presence of these remains on the southern hemisphere represents one of the most complete records of a Mosasaurus mosasaur. Fil: González Ruiz, Pablo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Museo de Historia Natural de San Rafael - Ianigla | Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Museo de Historia Natural de San Rafael - Ianigla | Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Museo de Historia Natural de San Rafael - Ianigla; Argentina Fil: Fernández, Marta Susana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Talevi, Marianella. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina Fil: Leardi, Juan Martín. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de ...